Detection of APAF1 mutation in Holstein cows and mummified foetuses in Japanese dairy herds. (27th October 2017) - Ghanem, ME; Nishibori, M; Isobe, N; Hisaeda, K
Contents: Some of the highest genetic merit sires have been shown to harbour recessive mutations affecting fertility, which may spread rapidly in the population through AI. These disorders may result in abortion and decline in pregnancy per insemination in cows. This study was carried out on 240 Holstein‐Friesian cows and 15 mummified foetuses. Blood and tissue samples were collected from the cows and mummified foetuses, respectively, for DNA extraction. Allele‐specific PCR was designed for the detection of the cows and foetuses carrying the nonsense mutation (C/T) in apoptosis peptide activating factor 1 gene ( APAF1 ). The mutant allele frequency of the APAF1 in carrier cows and mummified foetuses was calculated. Milk samples were taken from the carrier and non‐carrier cows for progesterone assay. The allele‐specific PCR reaction efficiently distinguished the C/T mutation in APAF1 . Of 240 cows, seven cows (2.9%) were diagnosed to carry one copy of the mutant allele of APAF1 . However, the carrier frequency was 33.3% in mummified foetuses (five of 15). The mutant allele frequency was 0.02 and 0.17 in the cows and mummified foetuses, respectively. Concentrations of progesterone did not differ between cows with APAF1 mutation and non‐carrier cows during 45 days post‐insemination. This study provided allele‐specific PCR for the detection of APAF1 mutation in cows. Moreover, it reports the carrier and mutant allele frequencies of APAF1 in dairy cows and mummified foetuses in Japan.